DEVELOPMENT OF SUPPLEMENTARY BOOK “SPEAKING ONE” TO TEACH ENGLISH SPEAKING IN EXTRACURRICULAR GROUPS AT THE SENIOR HIGH SCHOOL OF RAUDLATUL ULUM GONDANGLEGI - Zainab Agustin; Widiarini Widiarini; Tyas Alhim Mubarok (Journey: Journal of English Language and Pedagogy, 2023)
This study aims to develop a Speaking One supplement book to complement student learning in the Extracurricular Group at the Senior High School of Raudlatul Ulum Gondanglegi. and determine the feasibility of teaching materials in the form of the Speaking One Supplementary book. The English Featured Program at Raudlatul Ulum Gondanglegi High School is a subject that all students must follow. However, in reality, several deficiencies were found in teaching speaking English: (1) the teacher's teaching methods were less varied (2) the books used for learning activities were still global in nature, and (3) learning to speak seemed monotonous. and bored. Research and Development (R&D), or research used to make certain goods and evaluate their feasibility. This research and development uses the ADDIE research model developed by Dick and Carry (1996). book validation results from media experts by 90% and from learning experts by 82.5. %. while the results of product trials conducted in two meetings amounted to 74.0625% The research and development results show that there is a significant effect of using the speaking supplement one book on student learning in English. In conclusion, the supplement book is an effective learning medium to complement student learning material in learning English speaking.